Odziv študentov na predavanje preko spletne videokonference - Bavec, Cene (Uporabna informatika (Ljubljana), 2005)
The paper presents research in which 73 undergraduate students of the Faculty of Management Koper assessed a lecture delivered by Web-videoconferencing system. Research was based on a single event that had not been announced in advance. As result, we could assess the effect of the first impression that plays an important role in psychological research showing subjective acceptance and expectance of new technologies. The result show a very positive attitude of the students and their acceptance of virtual learning environment. Their comments on the interaction between the teacher and students that can hardly be replaced by technology were also interesting.
Keywords: poučevanje; učenje na daljavo; videokonference; visoko šolstvo